Brand Image as a Mediator between Price Perception and Purchase Decisions: Evidence from Artshop Consumers in Ubud - Wayan Meryawan; Tjokorda Gde Agung Wijaya Kesuma Suryawan; Mahayanti Fitriandari; Ni Luh Devi Merayani (JURNAL ILMU MANAJEMEN, 2026)
This study aims to analyze the role of brand image in mediating the influence of price perception on purchase decisions at Paneca Collection Artshop in Ubud, Bali. This research is motivated by declining sales performance and preliminary indications that consumers have not fully perceived price, brand image, and purchase decisions positively. Drawing on Cue Utilization Theory, this study positions price perception as an extrinsic cue that helps consumers form brand evaluations and purchase decisions, particularly in the context of cultural retail. The study used a quantitative approach involving 100 consumers selected through purposive sampling. The data were analyzed using PLS-SEM. The results show that price perception has a positive and significant effect on brand image and purchase decisions. Brand image also has a positive and significant effect on purchase decisions and partially mediates the influence of price perception on purchase decisions. These findings confirm that purchase decisions in cultural retail are shaped by the interaction between rational price evaluation and symbolic brand evaluation. In practice, this study emphasizes the importance of aligning pricing strategies with consumers’ perceptions of value and strengthening an authentic brand image to encourage purchase decisions.